Soldat des 19. Jahrhunderts auf Reisen. Wanderung von Karl Gustav Wilhelm Prinz von Hohenlohe-Langenburg durch Europa (Theatrum historiae, 2013)
The article deals with travelling of prince Karl Gustav Wilhelm of Hohenlohe-Langenburg (1777–1866). He marched in the service of the Habsburg army nearly all European countries. In private, however, he travelled only to several family residences. The journey with his sister and her children from the Hague to Vienna (1808) created the only exception from this trend. The trips to family residences were motivated mostly by the need of his personal presence in different legal acts. He never travelled for fun.